A perspective on the expansion of the genetic technologies to support the control of neglected vector-borne diseases and conservation - Raban, Robyn; Gendron, William A. C.; Akbari, Omar S. (Frontiers in Tropical Diseases, 2022)
Genetic-based technologies are emerging as promising tools to support vector population control. Vectors of human malaria and dengue have been the main focus of these development efforts, but in recent years these technologies have become more flexible and adaptable and may therefore have more wide-ranging applications. Culex quinquefasciatus, for example, is the primary vector of avian malaria in Hawaii and other tropical islands. Avian malaria has led to the extinction of numerous native bird species and many native bird species continue to be threatened as climate change is expanding the range of this mosquito. Genetic-based technologies would be ideal to support avian malaria control as they would offer alternatives to interventions that are difficult to implement in natural areas, such as larval source reduction, and limit the need for chemical insecticides, which can harm beneficial species in these natural areas. This mosquito is also an important vector of human diseases, such as West Nile and Saint Louis encephalitis viruses, so genetic-based control efforts for this species could also have a direct impact on human health. This commentary will discuss the current state of development and future needs for genetic-based technologies in lesser studied, but important disease vectors, such as C. quinquefasciatus, and make comparisons to technologies available in more studied vectors. While most current genetic control focuses on human disease, we will address the impact that these technologies could have on both disease and conservation focused vector control efforts and what is needed to prepare these technologies for evaluation in the field. The versatility of genetic-based technologies may result in the development of many important tools to control a variety of vectors that impact human, animal, and ecosystem health.